2013
DOI: 10.1186/1744-9081-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Performance of conventional pigs and Göttingen miniature pigs in a spatial holeboard task: effects of the putative muscarinic cognition impairer Biperiden

Abstract: BackgroundThe pig is emerging as a model species that bridges the gap between rodents and humans in research. In particular, the miniature pig (referred to hereafter as the minipig) is increasingly being used as non-rodent species in pharmacological and toxicological studies. However, there is as yet a lack of validated behavioral tests for pigs, although there is evidence that the spatial holeboard task can be used to assess the working and reference memory of pigs. In the present study, we compared the learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…100% within 16 sessions of 13 trials) was observed with five months pigs by using an active-choice task. Although these older animals were already used in other cognitive experiments [ 40 ], authors suggested that active-choice tasks, for which responses are operant for the two trained cues (e.g. animals have to go-left to positive cues and have to go-right to negative cues), gave clearer and more consistent results than go/no-go tasks, especially because they allow differentiating a pessimistic response (approach of negative location/lever) from an omission.…”
Section: Discussionmentioning
confidence: 99%
“…100% within 16 sessions of 13 trials) was observed with five months pigs by using an active-choice task. Although these older animals were already used in other cognitive experiments [ 40 ], authors suggested that active-choice tasks, for which responses are operant for the two trained cues (e.g. animals have to go-left to positive cues and have to go-right to negative cues), gave clearer and more consistent results than go/no-go tasks, especially because they allow differentiating a pessimistic response (approach of negative location/lever) from an omission.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural paradigms for cognitive assessment in larger species have been reported from specialist centres for sheep, pigs and cattle [41, 4751]. The most advanced cognitive abilities are seen in primates, for which sophisticated cognitive tools have been developed [52, 53].…”
Section: Introductionmentioning
confidence: 99%
“…Sophisticated cognitive testing paradigms are available for primates 32, 52 . By contrast, cognitive paradigms for large domestic species are currently rudimentary 53, 54 .…”
Section: Discussionmentioning
confidence: 99%